Traditional Games in The Family and Development of Children’s Motor Skills: Literature Review and Case Studies - Dudi Komaludin; Agus Mahendra; Nurlan Kusmaedi; Amung Ma'mun (Universitas Pendidikan Indonesia, 2025)
Traditional games play a vital role in developing children’s motor skills, especially when practiced in a family setting. This article aims to examine the impact of traditional games within families on the development of children’s gross and fine motor skills through a literature review and case studies. The study employs a qualitative approach, combining the analysis of relevant literature and direct observation of families engaging in traditional games. The literature review identifies various traditional games that contribute positively to motor skill development. Games like jump rope, congklak (a traditional board game), and egrang (stilts) are known to improve coordination, balance, muscle strength, and agility. Case studies were conducted on several families who routinely played traditional games with their children. Observations revealed that children actively involved in traditional games exhibited better motor skill development than those less engaged in such activities. This article also highlights that parental involvement in traditional games not only strengthens family bonds but also creates a supportive environment for children’s motor skill development. This involvement includes active parental roles guiding and participating in the games, helping children understand the rules and enhancing their social skills. The article concludes by emphasizing the importance of traditional games within families as a tool for developing children’s motor skills. Hopefully, these findings will encourage families and educators to integrate traditional games into children’s daily activities as part of an effective motor development strategy. Further research is recommended to explore various aspects of traditional games and their impact on child development in different contexts.